Denmark : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Denmark. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the economic performance of Denmark. Although Denmark has a longstanding track record of sound economic and social policies, economic performance has been relatively weak for an extended period. The economy continues to grow slowly. After recording 1.3 percent growth in 2014, the economy grew by 1.2 percent in 2015, driven mostly by private consumption on the back of rising employment and real incomes. However, relatively strong performance in the first half of the year was partly undone by flagging exports in the second half of the year. Denmark has consistently run current account surpluses in recent decades, mostly reflecting structurally high retirement savings in the context of its funded pension system.